The Influence of Competency and Leadership Style on the Performance of Educational Personnel at HKBP Nommensen University Medan - Maris Stella Sitorus; Yeni Absah; Parapat Gultom (Proceeding of International Conference on Islamic Boarding School, 2025)
Competence and Leadership Style are two important elements that affect the performance of educational personnel. The purpose of this study is to determine the effect of competence and leadership style on the performance of educational personnel. Research Method The approach used in this study is quantitative. The type of data used in this study is primary data. The method used to collect data in this study is a questionnaire. The questionnaire was chosen because of its effective and efficient data collection in this technological era. The questionnaire will be given to respondents who meet the research criteria using a google form that is filled in under the supervision of the researcher when filling in so that it is easy to obtain accurate information. Research Results based on the results of the hypothesis testing analysis, it can be concluded that Competence (X1) and Leadership Style (X2) partially and simultaneously affect the Performance of Educational Personnel with an R2 value of 0.485. The coefficient value obtained shows that Digital Leadership and Online Training are able to influence changes in the Performance of Educational Personnel by 48.5%, while the remaining 51.5% of other contributions are influenced by other variables that are outside the measurement framework used in this research.